A simple way of improving graphite nanoplatelets (GNP) for their incorporation into a polymer matrix - H. Persson; Y. Yao; U. Klement; R. W. Rychwalski (eXPRESS Polymer Letters)
A simple method of solvent exfoliation/refining of direct-graphite nanoplatelets for their better incorporation into a polymer matrix is presented. We demonstrate the method for polystyrene. The method relies on sonication in N-methyl-2-pyrrolidone solvent, with surfactant assistance. A small amount of polystyrene is added to the solvent in order to increase the viscosity, this enhancing the exfoliation process and resulting in formation of a polymeric layer on graphene for its better incorporation in the polymer matrix. Polystyrene-coated thin graphene stacks form a stable dispersion, while thicker graphite nanoplatelets settle out. Thus bulk separation of thin and thick graphene stacks takes place. The polystyrene-coated thin graphene stacks are studied using Transmission Electron Microscopy in two ways: (i) we calculate the number of graphene layers forming thin graphene stacks, and (ii) we employ Selected Area Diffraction to confirm our image analysis results by checking the intensity ratio (1100) and (2100) deflections in the diffraction patterns. Five layers is found to be the cut-off number, that is there are no stacks >5 layers, and 3 layer stacks are dominantly present. The average largest in-plane dimension is found to be approximately 2.5 µm (reduction by 50%).